Implications of quarantine among healthcare professionals: findings from a scoping review. Issue 10 (26th November 2022) - Bressan, Valentina; Mansutti, Irene; Longhini, Jessica; Moreale, Renzo; Caruzzo, Davide; Libriani, Silvia; Danielis, Matteo; Palese, Alvisa
Abstract: Although quarantine has been largely used in the recent period of novel coronavirus disease (COVID-19), there has to date been no summary of the available literature regarding its implications among health care workers (HCWs). A scoping review was performed, following The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review and the Joanna Briggs Institute Critical Appraisal Checklist. The CINAHL, PubMed, and SCOPUS databases were queried up to 31 January 2021. Nine studies ranging from low to high methodological quality, were included. These were conducted in diverse countries, predominantly regarding the Severe Acute Respiratory Syndrome and using cross-sectional designs. Quarantine was found to have multifaceted negative consequences that affected HCWs psychologically, professionally, personally, socially and economically. These findings could be useful as a framework for researchers while designing future study protocols, and for policy-makers or managers while establishing multidimensional effective strategies increasing HCWs' resilience and wellness.